Reproductive management and performance of crossbred mares and PO of Quarter Horses in farms located in the brazilian semiarid (Research, Society and Development, 2020)
In the northeastern semi-arid region, the conditions for breeding horses for reproductive purposes and for the practice of vaquejada must be understood in order to correct limiting factors and adopt measures that maximize the quality of the products. In these conditions, the objective of this work was to characterize the management practices and the reproductive performance of crossbred and PO horses of the Quarter Horse breed in stud farms located in the states of PB, PE and RN. 399 crossbred mares and PO of the Quarter Horses were evaluated for nutritional, health management and reproductive efficiency indexes such as: pregnancy rate (TP), embryo recovery rate (TR), birth rate (TN) and rate service (TS). Of this total, 47 Quarter Horses PO mares were evaluated for age at first calf (IPC), interval between births (IEP), number of births (NC). The values of the variables between the groups were submitted to the Chi-square test. The IPC and IEP data were subjected to analysis of variance followed by the Tukey test. There was no difference (p